2007
DOI: 10.1016/j.jana.2007.01.008
|View full text |Cite|
|
Sign up to set email alerts
|

Culture-Specific Factors Contributing to HIV Risk Among Jamaican Adolescents

Abstract: The purpose of this article is to describe the results from an elicitation research study addressing the multisystem-level factors that contribute to HIV risk among Jamaican adolescents. Focus group and survey data were determined from parents, adolescents, and teachers in Kingston, Jamaica, from 2004 and 2005. Guided by an ecological extension of the Theory of Planned Behavior, focus groups and survey questionnaires identified cultural factors at the individual, family, and societal levels that significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Hutchinson et al (Hutchinson, 2007) conducted an elicitation study in Jamaica with adolescents to learn more about cultural factors affecting their HIV-risk behaviors. These authors found that cultural beliefs affect condom use, sense of control over personal actions and also drive myths about transmission and "cure".…”
Section: Discussionmentioning
confidence: 99%
“…Hutchinson et al (Hutchinson, 2007) conducted an elicitation study in Jamaica with adolescents to learn more about cultural factors affecting their HIV-risk behaviors. These authors found that cultural beliefs affect condom use, sense of control over personal actions and also drive myths about transmission and "cure".…”
Section: Discussionmentioning
confidence: 99%
“…use condom or have no multiple sexual partners) (Ajzen and Fishbein, 1980). The TRA proposes that intentions are, in turn, influenced by the individual's behavioural beliefs or attitudes about the behaviour and his or her normative beliefs regarding the behaviour (Hutchinson, et al, 2007). The theory states that if people evaluated the suggested behaviour as positive (attitude), and if they think their significant others wanted them to perform the behaviour (subjective norm), this results in a higher intention (motivation) and they are more likely to do so (behaviour).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, given a sufficient degree of actual control over the behaviour, people are expected to carry out their intentions when the opportunity arises (Ajzen, 2006 (Jemmott et al, 2001). Hutchinson et al (2007) noted that within the TPB, behavioural, normative, and control beliefs are viewed as the sole determinants of intentions and behaviours and all other factors are viewed as external influences that act through their influence on these three constructs.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…For the 30% of the population in the English-speaking Caribbean who are adolescents and youth, sexual development occurs against a backdrop of regional instability and numerous challenges to health and development. Approximately one-third of adolescents in this region have had sexual intercourse, with many debuting at early ages; on average, boys at age 11 and girls at ages 14 -15 [1][2][3][4][5][6][7]. Moreover, studies report that among adolescents who are sexually active, one-third have had multiple sexual partners in the past year, 90% have used condoms, but only 16%-25% have used them consistently, and approximately half of those who are sexually active reported that their first sexual intercourse was forced [1][2][3].…”
mentioning
confidence: 99%